Situation of Southeastern Anatolia in Thymus Surgery: To Whom, Why, and How Thymectomy Was Performed: Thymus Surgery in Southeast Anatolia - Elma, Bekir; Tunçözgür, Bülent; Şanlı, Maruf; Işık, Ahmet Ferudun (European Journal of Therapeutics, 2021)
Objective: We sought to obtain information on the number of thymic lesions, surgical method, histopathology. We also investigated the relationship between thymic lesions and myasthenia gravis. Methods: We retrospectively examined patients who underwent thymectomy for different thymic pathologies in our clinic between February 1998 and April 2014 according to their demographic characteristics, symptoms, surgical method, resection width, and histopathological diagnosis. Results: The proportion of men and women was similar. The average age was 40.6±14.7 years. The most common symptom was rapid fatigue and the most common surgical method was median sternotomy. During extended thymectomy, we resected and recontructed the anatomical structures. We found a high degree of association between thymoma and myasthenia gravis. The average life expectancy of the patients was 171.8±8.8 months. Conclusion: Although the indications of thymectomy are not well known, the surgical procedures vary. We would therefore continue developing ourselves as the center where these surgeries are most frequently performed in the Southeastern Anatolia Region.